The use of coherent anti-Stokes Raman Spectroscopy as a diagnostic technique for studying the hydrogenation of carbon moxide in a tube-wall reactor - Simon, Russell James (Department of Chemical Engineering, 2026)
The methanation reaction, discovered in 1902 by Sabatier and Senderens, still remains a subject of intense interest. It is currently used in numerous industrial processes to remove carbon monoxide traces in hydrogen-rich gases of ammonia plants. Since the early 1980's there has been a renewed interest in especially catalytic methanation as it is an important step in the transformation of coal into substitute natural gas - an industrial process that is becoming more attractive to coal~rich developing countries. Current reactors are of the fixed bed type, but there is an interest in using tube-wall reactors in order to reduce the large pressure drops normally associated with fixed bed reactors. Coherent Anti-Stokes Raman Spectroscopy (CARS) is a relatively new laser-based spectroscopic technique which may be used to obtain the concentrations of species in the gas phase. The aim of this work was to study the methanation reaction over various supported metal catalysts in a simple tube-wall flow reactor using CARS. The metals, nickel,cobalt and ruthenium were used to catalyse the methanation reaction. These were loaded onto various amorphous and zeolitic supports using typical ion exchange and incipient wetness techniques. The metal loading of the catalysts were determined by atomic adsorption analysis. Typically, the metal loadings were 7% and 0.5% by mass.